(untitled) (TEST Antologia di Diritto Pubblico, 2024)
The essay, edited by Prof. Fulco Lanchester, foretastes the theme of the next issue of the Journal and aims to analyze the reflections carried out in V.E. Orlando,V.E. Orlando, Del fondamento giuridico della rappresentanza politica, in Id., Scritti vari di Diritto pubblico generale (1881-1940), coordinati in sistema, Milan, Giuffrè, 1940, unaltered reprint 1954, pp. 417-456